2019
DOI: 10.3389/fneur.2019.01041
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of GLT-1 via PI3K/Akt Pathway Contributes to Neuroprotection Induced by Dexmedetomidine

Abstract: Perioperative ischemic stroke usually leads to neurological dysfunction caused by neuron death. During the ischemic condition, excitotoxity due to extracellular glutamate accumulation is a main mechanism of neuron damage. The clearance of glutamate mainly depends on glutamate transporter-1 (GLT-1) which is expressed in astrocytes. Dexmedetomidine, an α2 adrenergic receptor agonist, is proved to induce neuroprotection. This study was set out to investigate the glutamate-related mechanism involved in the neuropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The phosphatidylinositol 3-kinase (PI3K)/protein serine threonine kinase (AKT) pathway is an important signaling pathway in cells [11][12][13] . Activation of the signaling pathway can inhibit a variety of stimulationinduced apoptosis mechanisms and promote cell cycle progression, thereby promoting cell survival and proliferation while participating in angiogenesis 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The phosphatidylinositol 3-kinase (PI3K)/protein serine threonine kinase (AKT) pathway is an important signaling pathway in cells [11][12][13] . Activation of the signaling pathway can inhibit a variety of stimulationinduced apoptosis mechanisms and promote cell cycle progression, thereby promoting cell survival and proliferation while participating in angiogenesis 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Cells were sub-cultured once every 3 days, and only those in the exponential growth phase were utilized in experiments. Cells were seeded in 6-well plates at a density of 5×10 5 /ml (2 ml per well) or in a 96-well plate at a density of 1×10 5 /ml (100 ul per well) and subsequently incubated for 24 h.…”
Section: Cell Culturementioning
confidence: 99%
“…During cerebral ischemia, GLU is released in large quantities and accumulates in the synaptic cleft, followed by overwhelmed activation of GLU receptors, resulting in neuronal necrosis and apoptosis, which is called GLU excitotoxicity [5]. Excessive GLU can over-activate the NMDA receptors of neurons and cause oxidative stress and calcium overload [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is critically urgently to investigate the unearthing the underlying mechanism behind HIBD. Dexmedetomidine (DEX), a novel sedative-analgesic agent, is regarded as a highly specific and selective a2-adrenoceptor agonist which has sedative, analgesic, and anxiolytic properties, and it is commonly used in clinical practice as an anesthetic (Peng et al, 2019). In recent years, increasing studies indicated that DEX can provide neuroprotective effects against HIBD in multiple ways, such as inhibition of apoptosis, blocking the release of inflammatory cytokines and relieving oxidative stress, which also is able to improve the cognitive function under the condition of hypoxia-ischemia (Degos et al, 2013;Ren et al, 2016;Akpınar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%